"before midnight she had miscarried": Women, Men, and Miscarriage in Early Modern England. (January 2015) - Evans, Jennifer; Read, Sara
Reproduction and childbirth in the early modern era have sometimes been represented as a uniquely feminine experience. Similarly, studies of domestic medicine have in the past overlooked the role that men played in domestic health care practices. This article builds on recent work that resituates men within both of these discourses by considering the ways in which men understood, discussed, and responded to the threat and occurrence of miscarriage in the women they knew. It considers a range of medical literature, spiritual diaries, and letters to illustrate that men were a central feature of many women's experiences of miscarriage.